The Effect of Student Guidance Policy Implementation on Student Management on the Discipline of Students in Public Junior High Schools in Madiun City - Nunuk Dwi Hidyawati (International Journal of Education, Language, and Religion, 2025)
This study aims to analyze the effect of implementing student guidance policies in student management on the discipline of students in public junior high schools in Madiun City. The research employs a quantitative descriptive method using a survey technique with a sample of 367 students from grades 7, 8, and 9. Data collection was conducted through validated and reliable questionnaires. The findings reveal a strong correlation (Pearson correlation = 0.660) between the implementation of student guidance policies and student discipline, indicating that well-executed policies significantly influence student behavior. The student guidance policies evaluated include enforcement of school rules, character development programs, strict attendance monitoring, and consistent application of sanctions and rewards. The results emphasize the importance of comprehensive student management policies in fostering disciplined behavior, supporting the notion that student development requires active collaboration among schools, teachers, and stakeholders. These findings align with the theoretical framework that structured and continuous guidance creates a conducive and orderly learning environment